Feasibility of time-lapse VSP monitoring at the Aquistore CO2 storage site using a distributed acoustic sensing system. (July 2016) - Harris, Kyle; White, Don; Melanson, Dave; Samson, Claire; Daley, Thomas M.
Highlights: DAS VSP is a feasible technique for reservoir monitoring at the Aquistore project. Modeling/repeatability results show minimum of 27 kt of injected CO2 for visibilty. Individual decameter-thick CO2 layers can be imaged in reservoir with DAS VSP. Abstract: The Aquistore carbon storage project, located near Estevan, Saskatchewan, Canada, aims to employ 3D time-lapse seismic techniques to monitor injected CO2 at depths of 3100–3350 m. During early stages of the injection schedule, vertical seismic profiling (VSP) will primarily be utilized, given its inherent advantages in imaging close to the borehole. Distributed acoustic sensing (DAS) possesses the capability of providing a cost-efficient, high-resolution alternative to traditional geophone methods in VSP. In this study, an evaluation is made of baseline DAS and traditional geophone VSP data from an observation well located 150 m away from the injection well. Comparative images are analyzed for quantities of injected CO2, ranging from 27 kt to 330 kt to determine the visibility of the CO2 plume over time. The study demonstrated that DAS VSP is a feasible technique for reservoir monitoring at the Aquistore site. The CO2 plume should be visible near the borehole after 90 days (27 kt of CO2 ) of injection, with increasing clarity over a three-year duration.